Pengembangan Media Pembelajaran Simulator Global Warming untuk Meningkatkan Hasil Belajar IPA - Astutik, Ida Sri (Jurnal Didaktika Pendidikan Dasar, 2019)
Science learning on changes in natural appearance material in the 5th grade of SDN Kwadungan is still not optimal. It is proved by the achievement of classical completeness that is only 55% with an average score of 69.00. The purpose of this study is to develop and to evaluate the use of the Global Warming Simulator and to improve science learning outcomes. Global Warming Simulator is a learning media in the form of two miniatures about the appearance of nature. The first miniature is the appearance of a nature sight that is still original and has not been affected by global warming, while the second miniature is the appearance of nature sight that has been affected by global warming. The results of this study indicate an improving learning outcome in science after the use of the Global Warming Simulator in the learning activities. The achievement of classical completeness has increased from 60% with an average value of 72.3 at the first meeting to 83.30% with an average value of 80.13 at the second meeting. This indicates that the use of Global Warming Simulator in science learning can improve student learning achievement.